PERLINDUNGAN HUKUM TERHADAP PARA PIHAK DALAM PEMBIAYAAN KONSUMEN - Prasetyawati, Endang (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2012)
Abstrak Process contract in consumer finance supposed through three stages that is, stage pre-prosperous contract, phase of the contract and phase after contract. Many factors that can give an indication of any abuse of power economy, in a stage pre-prosperous contract and phase contract from the company consumer finance while in the stage after company contracts consumer finance in position weak. Therefore not only consumer that need legal protection but also businessmen.Key words: Legal protection, consumer, businessmen.